Teachers; role in implementation of daily living skills curriculum for learners with mental challenges - Odera, Samuel Oti; Omoke, Charles Makori; Odongo, Charles Benson (The International Journal of Social Sciences and Humanities Invention, 2016)
The role played by teachers in the implementation of activities of daily living skills especially on learners with mental challenges cannot be overemphasized. Despite the government efforts to develop Daily Living Skills curriculum for the mentally challenged learners which was meant to improve the learners self-help skills, learners in special units are still unable to master skills such as shoe lacing, drooling control, brushing of teeth among others. This case study design within a qualitative approachframed from behaviourist social learning theory of Albert Bandura, aimed at establishing teachers’role in the implementation of daily living skills curriculum for children with mental challenges in special units in Rarieda sub-county. The objectives of the study were; to identify teaching methods employed by teachers to teach Daily Living Skills; to establish teachers’ perspectives on the teaching of Daily Living Skills; identify challenges facing teachers while teaching Daily Living Skills; and to find out the strategies teachers are using in implementing Daily Living Skills curriculum. The target population in this study was eighteen (18) participants comprising of five head teachers, eight teachers and six education officers. The study used purposive and saturated sampling techniques to select the sub-county, special units, head teachers, teachers and zonal quality assurance and standards officers to give a total of nineteen (18) participants. The study used interviews schedule, focus group discussion, and document analysis to obtain the data. The data were reported in verbatim and coded according to themes in the objectives, and analysed using thematic analysis and content analysis approaches. Trustworthiness and Authenticity of qualitative instruments was ensured by using multiple sources of data.The study revealed that teachers were using varieties of methods to teach Daily Living Skills, head teachers were not showing love and concern. There was also lack of teaching learning materials, poor remuneration and teachers in the special units borrow teaching learning materials to teach Daily Living Skills on mentally challenged learners
A case of special units in Rarieda Sub-County, Siaya County
Keywords: Daily Living Skills Curriculum; Learners with Mental Challenges